TTR Gly83Arg Mutation: Beyond Familial Vitreous Amyloidosis - Li, Zhenxian; Du, Kang; Chu, Xujun; Lv, He; Zhang, Wei; Wang, Zhaoxia; Yuan, Yun; Meng, Lingchao (Frontiers in Neurology, 2022)
Background Gly83Arg variation is a type of TTR mutation specific to the Chinese population. Patients of hereditary transthyretin amyloidosis (ATTR) with Gly83Arg variation predominantly present with blurred vision and most of these cases are reported by ophthalmologists. There is currently no systematic assessment of extraocular features of ATTR with Gly83Arg variation. Methods Six patients and two asymptomatic carriers with molecularly confirmed Gly83Arg variation of ATTR from three unrelated families were identified by sequencing the TTR gene. The clinical, electrophysiological, ultrasonic, and pathological data were collected and analyzed. Results This study included six patients and two carriers with TTR Gly83Arg mutation, all of whom came from the Han nationality of China. The average age of onset for the six patients was 39 years, and the course of disease ranged from 5 to 19 years. All the patients started with blurred vision, which was diagnosed as vitreous opacity (VO). Most of the patients developed sensory-motor polyneuropathies over years or even more than a decade (4–15 years) after VO. However, the heterogeneity of peripheral neuropathies among these patients remained large between families. Autonomic impairment also occurred after VO, with varying degrees of abnormalities seen in the associated autonomic assessments. None of the patients had any symptoms of cardiac impairment, but abnormal results were found in examinations. A combined biopsy of the sural nerve and muscle was also performed. Nerve pathology revealed the moderately reduced myelinated nerve fiber density and muscle pathology showed predominant neurogenic impairment accompanied by possible myogenic impairment. Conclusions This is a detailed account of Gly83Arg mutation-related ATTR, focusing on the extraocular presentations of this special variant in Chinese. Clinical features of this variant are early-onset, ocular involvement predominance, neurological, and cardiac involvement along with the disease, and relatively long survival.